Impact of fibronectin type III domain-containing family in the changes in metabolic and hormonal profiles during peripartum period in dairy cows - Daudon, Mathilde; Ramé, Christelle; Estienne, Anthony; Price, Christopher; Dupont, Joëlle (Frontiers in Veterinary Science, 2022)
The peripartum period in dairy cows is frequently associated with excessive lipolysis due to Negative Energy Balance (NEB). These metabolic disorders are the cause of various pathologies. Some metabolites such as β-hydroxybutyrate (BHBA) and Non-Esterified Fatty Acids (NEFA) are known to be biomarkers of NEB in dairy cows. The involvement of adipokines, including adiponectin and leptin, during fat mobilization in the peripartum period is well described, but little is known about the impact of myokines at this time. Fibronectin type III domain-containing proteins (FNDC) are myokines and adipokines recently discovered to play a role in metabolic dysfunctions. This study aimed to evaluate some FNDCs (FNDC5, 4, 3A and B) as potential plasma and adipose tissue indicators of NEB in cattle. We measured plasma FNDC concentrations and adipose tissue FNDC gene expression during the peripartum period, 4 weeks before the estimated calving day (4WAP), one (1WPP) and 16 (16WPP) weeks postpartum in two groups of dairy cows with low NEB (LNEB, n = 8) and high NEB (HNEB, n = 13) at 1WPP. Using specific bovine ELISAs, only plasma FNDC5 concentrations varied during the peripartum period in both LNEB and HNEB animals; concentrations were higher at 1WPP as compared to 4WAP and 16 WPP. FNDC5 plasma concentrations was negatively correlated with dry matter intake, live body weight, variation of empty body weight and glucose concentrations, and positively correlated with plasma non-esterified fatty acids and BHBA concentrations. Subcutaneous adipose tissue contained abundant FNDC5 mRNA and protein, as measured by RT-qPCR and immunoblotting, respectively. We also observed that FNDC5 mRNA abundance in subcutaneous adipose tissue was higher at 1 WPP as compared to 4WAP and 16WPP in HNEB cows and higher at 1 WPP as compared to 4 WAP in LNEB cows, and was higher in HNEB than in LNEB animals during early lactation. Finally, we showed that recombinant human irisin (a fragmented product of FNDC5) increased the release of glycerol and abundance of mRNA encoding adipose triglyceride lipase and hormone-sensitive-lipase in bovine and human adipose tissue explants. In conclusion, FNDC5 is expressed in bovine adipose tissue and may be involved in lipid mobilization and regulation of NEB in cattle.